Dzimulīdztiesības vērtējums sieviešu pašvaldību vadītāju skatījumā - Zaķe, Agate (Latvijas Universitāte, 2007)
Maģistra darbā „Dzimumlīdztiesības vērtējums pašvaldību vadītāju sieviešu skatījumā” apskatīti dzimumlīdztiesības teorētiskie aspekti un prakse, par pamatu ņemot feminisma un līderisma teorijas un dzimumlīdztiesības problemātikas skaidrojumu, aplūkoti kavējošie faktori sieviešu dalībai politikai, tādi kā stereotipi, sociālās lomas un to konflikti, kā arī dzimumdiskriminācija, skaidrota pašvaldība kā vietējā vara. Darbā ietverti arī jautājumi par ārvalstu pieredzi dzimumlīdztiesības stiprināšanā un Latvijas praksi dzimumlīdztiesības jautājumu problemātikā. Darbā izvirzītā hipotēze pierādīta, balstoties uz kvalitatīvi kvantitatīvu pētījumu: intervijas ar sievietēm pašvaldību vadītājām, sieviešu pašvaldību vadītāju anketēšana un vīriešu – pašvaldību vadītāju aptauja.

The Master Paper titled “Evaluation of Gender Equality in the Point of View of Women as Leaders of Local Authorities” deals with theoretical and practical aspects of gender equality issues based on feminism and leaderism theories and the explanation of problems concerned with gender equality, it also characterizes the disturbing factors for women participation in politics, namely, stereotypes, social roles and their conflicts, and gender discrimination, moreover, it provides explanations for the meaning of local authority being a local power. The Paper also includes issues regarding foreign experience related to strengthening of gender equality and Latvia’s practice in dealing with the gender equality problems. Hypothesis raised by this Paper is proved by a quantitative study: interviews with women who are leaders of local, questionnaires distributed to women who are leaders in local authorities and men who are also leaders in local authorities.
Evaluation of gender equality in the point of view of women as local government leader
Keywords: Vadībzinātne